Pengaruh Hipertensi Terhadap Kejadian Stroke Iskemik di Puskesmas Kuta Makmur Aceh Utara Tahun 2023 - Khairina Khairina (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2023)
Stroke is an acute clinical manifestation resulting from neurological dysfunction in the brain, spinal cord and retina, either partial or complete, that persists for 24 hours or causes death due to blood vessel disorders. According to the American Heart Association (AHA), in 2015 the prevalence of stroke reached 33 million patients worldwide. According to Basic Health Research (Riskesdas) in 2007, the national prevalence of stroke was 8.3 per 1,000 population. The highest stroke prevalence was found in Aceh (16.6 per 1,000 population) and the lowest in Papua (3.8 per 1,000 population). Many factors can influence the incidence of stroke, one of which is hypertension. Hypertension is a major risk factor for stroke. Often referred to as the silent killer because hypertension increases the risk of stroke by 6 times. It is said to be hypertension if blood pressure is greater than 140/90 mmHg. Stroke cases are included in the Doctor Competency Standards with grade 3B, which means a general practitioner must be able to make a clinical diagnosis based on anamnesis, physical examination and simple additional examinations. The general practitioner must be able to decide and provide preliminary therapy, as well as refer to relevant specialists (emergency cases).